The dream catcher - Motana, Nape'a,1945- (Department of English Language and Literature, 2014)
The dissertation is about an ambitious, rural young woman who aspires to be a great performing artist. Rabeka Maru-a-pula, spurns a marriage proposal, from an eligible bachelor attending her church because she feels that marriage will be an impediment to her unrealised dreams. Her parents are very upset by her decision. She meets her former teacher, TM who, appreciative of her amateur acting experience, invites her to join his project, 'Realise Your Dream.' This step initiates a lasting friendship from which she will draw support and encouragement when she encounters trials in the future.